Case study: the marketing strategy for China Unicom - Yajid, Mohd Shukri Ab; Sakinah,; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
China United Telecommunications Co., Ltd. (“China Unicom”) was established on July 19, 1994 by the state Council, as the only Chinese operator that has a license to provide a full range of services, the second national carrier to provide basic and value-added service, mobile, and telecom networks such as mobile and engineering service, and to provide long distance and local phone services to the general public. The finding of this study is that there is several factors affect China Unicom marketing strategy. China became a member of the world Trade Organization (WTO), the uncertainty policy by government and the bad performance of CDMA service are main factors that affect the company’s marketing strategy. This paper takes a fresh, in depth look at China Unicom and the issues it face, and provides insight into the future shape of China Unicom marketing strategy (X. Zhang & Prybutok, 2005; De Silva et al., 2018a; De Silva et al., 2018b; Nikhashemi et al., 2013).